(untitled) (Research, Society and Development, 2022)
The present study aims to expose the issue of challenges in dental management during endodontic treatment performed in a child patient. In view of the theme, it is emphasized that the work is based on an experience report, that is, the present theme will be discussed combining theory with practice. In this way, it is important to highlight the theme in its relevance, since the treatment of a child patient differs from that of an adult patient, this because of the creation of bonds that must occur in a humanized way so that the result is successful, in particular, he mentions endodontic treatments are used, this is because it is a procedure that requires greater attention and adequate management in child patients. Thus, it is important to note that the procedures performed on a child patient must follow the correct techniques, as well as the professional being attentive to provide good care, since any failure can lead to a lifelong fear of the dentist. In this way, the text will show the importance of good management in endodontic treatment when it comes to children, as well as the techniques to be used, as well as the importance of the responsible participation during the process of this treatment. Finally, the conclusion will show that the endodontic procedure in a child patient is something of great importance, with the correct use of techniques and also a humanized reception from the office to the incentives for the child to return to the consultations always motivated.